ASUHAN KEPERAWATAN IBU NIFAS DENGAN POST SECTIO CAESAREA : STUDI KASUS - Yeni Rimadeni; T. Iskandar Faisal; Halimatussakdiah Halimatussakdiah; Afdhal Afdhal; Nur Hartika (Journal Keperawatan, 2022)
Sectio Caesarea (SC) is a hysterotomy to deliver the fetus from inside the uterus. The impact that occurs in postpartum mothers with post sectio caesarea is acute pain and the risk of infection and skin integrity disorders that occur due to surgical wounds on the abdomen. To overcome the impacts that arise, it is necessary to have the role of nurses in providing comprehensive nursing care for postpartum mothers with post sectio caesarea, so as to prevent problems in postpartum mothers post sectio caesarea. Early mobilization is a policy to guide the patient to be able to move and walk from bed. The purpose of this study was to provide an overview of nursing care for postpartum mothers after sectio caesarea. This research method is descriptive in the form of a case study with a nursing process approach including assessment, nursing diagnosis, intervention, implementation and evaluation. The sample is Mrs. A 27 years old in the Obstetrics Room at Dr Zainoel Abidin Hospital, Banda Aceh. The results of the study found Mrs. A after nursing care for three days the barriers to physical mobility and the risk of infection were resolved and partially resolved. Conclusion: acute pain, physical mobility barriers and risk of infection.